Transferring Results of Professional Development into Practice: A Scoping Review - Dita Nīmante; Maija Kokare; Sanita Baranova; Svetlana Surikova (Education Sciences)
The paper aims to map available evidence regarding the transfer of learning from professional development (PD) into practice. The scoping review is based on an analysis of the key characteristics of effective PD, drawing from 60 meta-analyses and various types of reviews (e.g., systematic, integrative, etc.) regarding PD both in general and in various professional fields published from 2009 to 2024. Three research questions are put forward: What characterises effective PD? Which theoretical concepts in the scientific literature represent the transfer of adult PD into practice? And what processes and indicators show effective ways of transferring PD and learning outcomes into practice? The methodology of the review is organised into three steps—preliminary study, the main study, and conceptualisation—by selecting publications and deriving concepts and conclusions relevant to the research questions, as well as identifying knowledge gaps for further exploration. The research literature uses various concepts to characterise the transfer of PD into practice as it is determined by different contexts, research traditions, and practices. Although effective PD has been defined and several theoretical models have been developed, research on PD effectiveness indicators and processes related to the transfer of PD into practice is still ongoing. However, not all evaluations take these models as bases to evaluate the existing PD practices, so the different indicators proposed by different researchers make it difficult to compare the results. The main problem is insufficient evidence in terms of measurable and comparable effectiveness criteria in all fields. The scoping review reveals a variety of controversial or incompletely researched aspects of transferring PD results into practice.